Exploring AI Capabilities in Arabic Grammar: Comparative Analysis of ChatGPT and Gemini - Maulidiya, Amanda Resti; Abdurrahman, Maman; Saleh, Nalahuddin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study aims to compare the performance of ChatGPT and Gemini in analyzing i'rāb Marfû’ât al-Asmâ’', a critical aspect of Arabic grammar for determining the grammatical roles of words in sentences. The analysis uses 11 examples from the book Mulakhash Qawâ'id al-Lugah al-'Arabiyyah by Fuad Ni'mah, focusing on identifying grammatical components such as mubtada', khabar, isim ashbah, isim kāda, khabar inna, fā'il, nā'ib al-fā'il, na'at, 'atf, tawkid, and badal. The study employs the Mann-Whitney test to assess statistical significance and the Cosine Similarity Index (CSI) to measure semantic similarity. Results show that ChatGPT outperforms Gemini with a significant value of 0.019, while the CSI score of 0.800 indicates high similarity between the models' outputs. ChatGPT excels in providing detailed and accurate analyses, while Gemini is more suitable for concise answers but may lack precision. These findings highlight the unique strengths of each model and underscore the necessity of manual correction to ensure the accuracy and relevance of results, particularly in technology-based Arabic grammar learning.